Estudio y diseño de los medios de comunicación industrial sobre sistemas de protección con IEDs en subestaciones de distribución - Rosero Topón, Jonnathan Jesús (2013)
The main objective of the power distribution companies nowadays is to bring reliability, efficiency quality of the service and electric power continuity to the final user. To have an improved quality of response on the field equipment, it is necessary to implement a more efficient control and command as well as handy protocols from the IEDs. Moreover, with these communications media seek to improve their response times; also to be responsive commanding their equipment; therefore, reducing any inconvenient that may happen at the distribution substations.